Characterization of a novel xylanase from Aspergillus flavus with the unique properties in production of xylooligosaccharides. (12th February 2019) - Chen, Zhou; Liu, Yangliu; Zaky, Ahmed A.; Liu, Lu; Chen, Yaoyao; Li, Siting; Jia, Yingmin
Abstract : A novel xylanase from the filamentous fungus Aspergillus flavus was purified and characterized as the β‐1, 4‐endoxylanase (designed as AfXynB) with a molecular mass (32.2 kDa), which is different from all of the previously reported xylanases from the same strain. AfXynB was optimally active at pH 7.5 and 55 °C, respectively. It was stable up to 50 °C within range of pH 4.0–9.5, and displayed an excellent tolerance to various cations, reagents, and proteases. AfXynB showed specific activity toward beechwood xylan but no detected activity toward CMC and p NP‐β‐D‐xylopyranoside. The xylanase is a typical endo‐xylanase; it could hydrolyze beechwood xylan to only yield xylobiose (X2) and xylopentaose (X5). Actually, this may be the first report for the endo‐xylanases that displayed such a unique hydrolytic property. These findings in the present study have great implications for its future applications of the novel xylanase.